Benjamin Franklin : creating a nation - Warrick, Karen Clemens (America's founding fathers, 2004)
Examines the life of American statesman Benjamin Franklin, focusing on his role in the creation of the United States and the formation of the new country's government. Includes source documents, a time line, and maps.